2014
DOI: 10.1371/journal.pone.0097502
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Repeated Acupuncture Stimulation Induces Habituation Effects in Pain-Related Brain Areas: An fMRI Study

Abstract: Most previous studies of brain responses to acupuncture were designed to investigate the acupuncture instant effect while the cumulative effect that should be more important in clinical practice has seldom been discussed. In this study, the neural basis of the acupuncture cumulative effect was analyzed. For this experiment, forty healthy volunteers were recruited, in which more than 40 minutes of repeated acupuncture stimulation was implemented at acupoint Zhusanli (ST36). Three runs of acupuncture fMRI datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 74 publications
(70 reference statements)
0
21
0
Order By: Relevance
“…This technique has been used to investigate correlations between acupuncture and brain activity. Interestingly, an increase in sensorimotor cortical activity along with decreases in limbic–paralimbic–neocortical activities was found in several studies . Hence, the observations suggest that not only sensory processing, but also emotional, and cognitive functions play an important role for acupuncture responses.…”
Section: Discussionmentioning
confidence: 79%
“…This technique has been used to investigate correlations between acupuncture and brain activity. Interestingly, an increase in sensorimotor cortical activity along with decreases in limbic–paralimbic–neocortical activities was found in several studies . Hence, the observations suggest that not only sensory processing, but also emotional, and cognitive functions play an important role for acupuncture responses.…”
Section: Discussionmentioning
confidence: 79%
“…This may explain why in the first four sessions of EA intervention, MEK1 activation in rats with EA was higher than that in CCI animals. A study showed that the cumulative effects in the process of repeated acupuncture stimulation may be an interesting characteristic of bimodal habituation [9]. In other words, information induced by repeated EA stimulation may form a type of habitual memory in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence demonstrated that the short-term effect of a single session of acupuncture stimulation differs from the cumulative effect of multiple sessions of acupuncture stimulation, which may depend on the differential modulation of immunologic factors and neurotrophic signaling molecules [79]. Our previous study showed that the cumulative analgesic effect of repeated electroacupuncture (EA) intervention in neuropathic pain rats is closely associated with its regulatory effects on natural killer cells as well as some splenic and plasma cytokines [10].…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture has numerous functions (1-3), including use as an auxiliary method of treatment for acute or chronic pain (4,5). Certain studies have proposed that acupuncture-induced analgesia is a complex physiological adjustment process that involves the entire nervous system, including the central nervous system (CNS) and the peripheral nervous system (6)(7)(8). Mechanisms underlying acupuncture are intimately associated with neurohumoral and neurotransmitter pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms underlying acupuncture are intimately associated with neurohumoral and neurotransmitter pathways. A number of studies have hypothesized that acupuncture may play a role in inducing analgesia (8)(9)(10)(11)). …”
Section: Introductionmentioning
confidence: 99%